Designing Inclusive Urban Places - Carrera, Letizia (Italian Sociological Review, 2022)
Cities have always been characterized by economic and cultural differences. More and more ethnic differences have progressively been added and very often combined to the others, generating a perverse multiplier effect of the social fragility of migrants. The model of territorial distance for decades “protected” cities from diversity, which was made “invisible” through its being relegated to the margins of the city itself. Today this model does not work any longer and the differences coexist in the same urban spaces. In the absence of an intercultural dialogue capable of building and reinforcing an attitude of “active engagement” of urban areas, the solution that is too often sought is the assimilatory integration, which reinforces the disadvantage of alterity. Instead, the tension towards more complex processes of inclusion implies the overcoming of the concept of foreigner and the recognition of diversity and alterity in the name of the right of recognition of diversity. The role of the third space becomes central, as a complex and dynamic result of the contamination among public, semi-public and private spaces that offer opportunities to stop and meet. Therefore, the strategies that can be activated in the cities are fundamental.[...]